Corporate Governance and Earnings Management in Taiwan: A Quantile Regression Approach - Chi, Ching-Wen; Hung, Ken; Liu, Shinhua (Journal of Accounting and Finance, 2020)
This study examines the effect of family ownership and board independence on earnings management using quantile regression. Based on a large sample of Taiwanese companies, our results show that the effects of family ownership and board independence on earnings management differ across quantiles. Higher family ownership and greater proportion of independent directors affect earnings management positively and negatively respectively for firms in the lower quantile, but not in the higher quantile. Our findings can reconcile the conflicting predictions by the agency and stewardship theories about the effectiveness of family ownership and board independence on earnings management, with implications for regulators.